2019
DOI: 10.21203/rs.2.220/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of pomegranate juice on cardiometabolic risk factors and biomarkers of oxidative stress and inflammation in hemodialysis patients, a crossover controlled trial

Abstract: Background: Pomegranate has antioxidant, cardioprotective, and anti-inflammatory properties. We questioned if pomegranate juice (PJ) benefits lipid profile and oxidative and inflammatory biomarkers of hemodialysis patients. Methods: The study had a crossover design. Hemodialysis patients (n=41) were divided into two groups: PJ-treated group who received 100 ml natural PJ immediately after their dialysis session three times a week and the control group who received the usual care. After 8 weeks, a 4-week washo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Two of them showed significant reduction in systolic blood pressure and one reported significant reduction in diastolic blood pressure. In a cross over trial, systolic(135.65 ± 8.47 vs. 128.96 ± 6.11 mmHg) and diastolic (97.73 ± 9.95 vs. 90.84 ± 6.86 mm Hg) blood pressure significantly decreased in the pomegranate juice group ( p < 0.001) after 8 weeks of using 100 mL pomegranate juice following each dialysis session Systolic blood pressure increased significantly in the control group and the difference between the pomegranate juice group and control group for both systolic (−6.97 vs. 0.97 mm Hg) and the diastolic (−6.88 vs. 0.98 mm Hg) blood pressure was significant ( p < 0.001) (Boldaji et al, 2019). Wu et al reported that daily use of pomegranate extract (1000 mg) for 6 months resulted in a decrease of systolic blood pressure and diastolic blood pressure by 13% ( p < 0.05) and 11% ( p < 0.05), respectively, in the pomegranate extract group, but did not change in the control group.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Two of them showed significant reduction in systolic blood pressure and one reported significant reduction in diastolic blood pressure. In a cross over trial, systolic(135.65 ± 8.47 vs. 128.96 ± 6.11 mmHg) and diastolic (97.73 ± 9.95 vs. 90.84 ± 6.86 mm Hg) blood pressure significantly decreased in the pomegranate juice group ( p < 0.001) after 8 weeks of using 100 mL pomegranate juice following each dialysis session Systolic blood pressure increased significantly in the control group and the difference between the pomegranate juice group and control group for both systolic (−6.97 vs. 0.97 mm Hg) and the diastolic (−6.88 vs. 0.98 mm Hg) blood pressure was significant ( p < 0.001) (Boldaji et al, 2019). Wu et al reported that daily use of pomegranate extract (1000 mg) for 6 months resulted in a decrease of systolic blood pressure and diastolic blood pressure by 13% ( p < 0.05) and 11% ( p < 0.05), respectively, in the pomegranate extract group, but did not change in the control group.…”
Section: Resultsmentioning
confidence: 98%
“…We also tried to obtain the full text, and the articles were managed using EndNote software. Finally, implementing the search strategy, we identified nine articles (7 RCTs) that fulfilled the eligibility criteria (Boldaji et al, 2019; Jafari, Fallah, Bahrami, & Lorigooini, 2020; Jafari, Fallah, Reyhanian, & Sarmast, 2020; Rivara et al, 2015; Shema‐Didi et al, 2013; Shema‐Didi et al, 2014; Shema‐Didi et al, 2012; Wu et al, 2015; Yavari et al, 2017) (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, high-density lipoprotein cholesterol was increased after PJ assumption, whereas total and low-density lipoprotein cholesterol were not affected. Systolic and diastolic blood pressure dramatically fell in the PJ condition, while total antioxidant capacity increased [121].…”
Section: Prevention Of Cardiovascular Diseasesmentioning
confidence: 91%